Curcumin-loaded emulsome nanoparticles induces apoptosis through p53 signaling pathway in pancreatic cancer cell line PANC-1 - Demirci, Zuleyha; Islek, Zeynep; Siginc, Halime Ilhan; Sahin, Fikrettin; Ucisik, Mehmet H.; Bolat, Zeynep Busra (PERGAMON-ELSEVIER SCIENCE LTD, 2025)
Pancreatic cancer is a global health problem with a poor prognosis, limited treatment options and low survival rates of patients. Thus, the exploration of novel treatment approaches is crucial. Curcumin shows promise in pancreatic cancer. Curcumin has anticancer properties promoting apoptosis through the p53 pathway. However, adverse effects and low bioavailability are curcumin's main drawbacks and its delivery by nanoparticles could improve its effectiveness as a treatment option. Curcumin-loaded emulsome nanoparticles (CurEm) have shown promise in colorectal, hepatocellular, and prostate cancers. This study aims to evaluate the anticancer potential of CurEm in pancreatic cancer cell line PANC-1. The cytotoxic effects of CurEm on PANC-1 cells show cytotoxicity in dose and time-dependent manner. The selected dose 30 mu M CurEm resulted spheroidal morphology in PANC-1 cells and colony forming and scratch assay conducted demonstrated significant growth inhibition and decrease in migration ability, respectively. Cell cycle analysis shows that CurEm induces G2/M arrest in PANC-1 cells. CurEm-treated PANC-1 cells showed a significant increase in p53 and Caspase 3 genes, while a significant decrease in Bcl-2 genes compared to untreated group. Western blot results showed parallel results to qPCR analysis for Bcl-2 protein levels. Interestingly, we saw low p53 protein levels in CurEm-treated PANC-1 cells. These findings shed light on the potential of CurEm as an effective and stable therapeutic approach for pancreatic cancer.
Keywords: Pancreatic cancer; Curcumin; Curcumin nanoformulation; p53 pathway; Anticancer therapy; EPITHELIAL-MESENCHYMAL TRANSITION; DOWN-REGULATION; BREAST-CANCER; EXPRESSION; INVASION; PROLIFERATION; DELIVERY; ARREST; ANGIOGENESIS; SOLUBILITY; Toxicology